Implications of International Tourist Levy Policy on Sustainable Tourism in Bali - Ni Putu Gita Puspadewi; I Ketut Wardana Yasa; I Made Gede Anadhi (International Forum of Researchers and Lecturers, 2025)
Bali tourism is currently facing challenges such as environmental degradation and overtourism due to the massive influx of visitors. As a solution that has been implemented in various countries, the Tourist Levy began to be applied in Bali on February 14, 2024, through Regional Regulation No. 6 of 2023, known as the Foreign Tourist Levy, with the aim of protecting Bali’s nature and culture towards quality tourism. This research becomes urgent to examine the implications of the foreign tourist levy on Bali’s sustainable tourism. Although this regulation has noble intentions, its implementation has generated various responses from international tourists and tourism stakeholders in Bali. This condition has prompted the author to conduct an in-depth study. The objectives of this research are: (1) To analyze the implementation of the foreign tourist levy (International Tourist Levy) policy in Bali, (2) To analyze the challenges in implementing the foreign tourist levy (International Tourist Levy) policy on sustainable tourism in Bali, and (3) To analyze the implications of the foreign tourist levy (International Tourist Levy) policy for international tourists and tourism stakeholders in realizing sustainable tourism. The method used in this research is a descriptive approach. The types of data employed are qualitative and quantitative data. Data collection methods include observation, interviews, questionnaires, and documentation, analyzed using qualitative descriptive data analysis techniques. The results of this study indicate that the International Tourist Levy has great potential in strengthening sustainable tourism in Bali. The majority of tourists support the sustainability goals of this policy, although some express concerns about the transparency of fund utilization and the impact of additional costs on travel decisions. Meanwhile, tourism industry players demonstrate positive adaptation, with emphasis on the need for strengthening socialization, transparency, and collaboration among stakeholders. This research recommends enhancing public communication and conducting regular evaluations of the policy to be more responsive to the dynamics and needs of tourists. Thus, this policy is expected to serve as a model for foreign tourists’ contributions in supporting the preservation of Bali’s cultural and natural heritage in a sustainable manner.